Indigo's Star - McKay, Hilary (London Hodder Children's Books, 2004)
It's two years since Saffy found her angel and now her brother Indigo, the only boy in the Casson family, has a quest of his own. He's helped by his new school pal and, of course, by Rose, his ever-resourceful younger sister. The eagerly-awaited sequel to the award-winning Saffy's Angel. ALSO AVAILABLE ON AUDIO AS A DOUBLE CASSETTE
Keywords: Children's stories